Muslim Medical Student Scale. - Musa, Ramli (2013)
International Islamic University Malaysia has pioneered the model of Islamic Input into Medical Program (IIMP). To date there are a number of medical schools around the globe that have introduced the IIMP module. However, many aspects of the module are not evidence based, simply because there is only a handful of research conducted in this area. On a positive note, we are beginning to see some movement in data collection and analysis of IIMP but the intensity is rather low. As far as the researchers are concerned, currently there are no tools that test the efficacy, professionalism and religiosity of Muslim doctors. There are several religiosity tools that test the religiosity of Muslim youth and Muslims in general, but there are no tools that specifically measure the religiosity and professionalism aspect of Muslim doctors. Another important aspect of this area is the end result of IIMP, i.e. the makeup of the graduates themselves. It is significant to investigate whether they have acquired the specifications in all the domains that constitute the makeup of a good and competent Muslim doctor. Hence, we plan to invent two new validated questionnaires to screen the achievements of practicing Muslim doctors and Muslim student doctors in this area. Copyright No CRLY 00000312